2000
DOI: 10.1161/01.str.31.9.2049
|View full text |Cite
|
Sign up to set email alerts
|

Deteriorating Ischemic Stroke in 4 Clinical Categories Classified by the Oxfordshire Community Stroke Project

Abstract: Background and Purpose-The aim of this study was to investigate the frequency, possible predictive factors, and prognosis of deteriorating ischemic stroke in 4 clinical categories according to the classification of the Oxfordshire Community Stroke Project (OCSP). Methods-A total of 350 patients with first-ever ischemic stroke who presented within 24 hours of onset were enrolled.Based on the OCSP criteria, cerebral infarctions were divided into the following 4 clinical categories: total anterior circulation inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
3
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 49 publications
3
103
3
2
Order By: Relevance
“…The frequency and significance of perfusion abnormality in LI was previously addressed in several small series. [26][27][28] One of the largest studies (22 patients) demonstrated MTT abnormality in 68.2% of LIs, comparing favorably with 61% in the present series.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The frequency and significance of perfusion abnormality in LI was previously addressed in several small series. [26][27][28] One of the largest studies (22 patients) demonstrated MTT abnormality in 68.2% of LIs, comparing favorably with 61% in the present series.…”
Section: Discussionsupporting
confidence: 64%
“…Other smaller studies report perfusion abnormality in 0% 26,28 to 100% 14 of cases. Clinically, perfusion abnormality in LI was previously shown to be associated with the persistence of symptoms beyond 24 hours.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…4 Among 350 Japanese patients in one study, 25% progressed after admission; worsening in the hospital occurred in 26% of lacunar stroke patients. 5 A number of studies focused on progression and worsening in series of patients with lacunar strokes. In a Spanish study of 225 lacunar infarct patients, the deficit accrued within hours in 50.5% and within days in 16%.…”
Section: How Common Is Worsening and In Whichmentioning
confidence: 99%
“…14 Clinical classification is also predictive of the risk of deterioration, with TACS having the greatest risk and LACS the least; deterioration is associated with a worse prognosis. 15 The relationship between clinical classification and degree and timing of stroke recovery is less clear, and has been further examined here using data from the 'Tinzaparin in Acute Ischaemic Stroke Trial' (TAIST). 16 …”
Section: Introductionmentioning
confidence: 99%